2022
DOI: 10.3389/fphy.2022.942486
|View full text |Cite
|
Sign up to set email alerts
|

Effects from dayside magnetosphere to distant tail unleashed by a bifurcated, non-reconnecting interplanetary current sheet

Abstract: Global magnetospheric effects resulting from the passage at Earth of large-scale structures have been well studied. The effects of common and short-term features, such as discontinuities and current sheets (CSs), have not been studied in the same depth. Herein we show how a seemingly unremarkable interplanetary feature can cause widespread effects in the magnetosheath-magnetosphere system. The feature was observed by Advanced Composition Explorer inside an interplanetary coronal mass ejection on 10 January 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…There are significantly fewer studies of the geoffectiveness of the solar wind DD than those of CMEs and CIRs. Farrugia et al (2022) observed the formation of complicated structures in the magnetotail and nightside ionosphere as a DD passes by the magnetosphere.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…There are significantly fewer studies of the geoffectiveness of the solar wind DD than those of CMEs and CIRs. Farrugia et al (2022) observed the formation of complicated structures in the magnetotail and nightside ionosphere as a DD passes by the magnetosphere.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Farrugia et al. (2022) observed the formation of complicated structures in the magnetotail and nightside ionosphere as a DD passes by the magnetosphere.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, SW is not a smooth, homogeneous flow, but consists of expanding flux tubes (Borovsky, 2008), IMF discontinuities and fluctuations (e.g., possibly different wavelength Alfvén and compressional waves) (Nykyri et al., 2019), 2‐D and slab turbulence (Adhikari et al., 2022), and advected SW plasma and magnetic field structures (Di Matteo et al., 2022; Viall & Borovsky, 2020; Viall et al., 2009). Recent studies showed that solar wind directional discontinuities can introduce significant perturbations to the magnetosphere and ionosphere even as the geomagnetic activities remain quiet (Farrugia et al., 2022; Wing et al., 2023).…”
Section: Introductionmentioning
confidence: 99%